Vulnerability assessment of water resources in a karst mountainous area based on GIS/RS technology: a case study of Guiyang, Southwest China. Issue 5 (18th March 2022) - Li, Wei; Zhao, Zulun; Lv, Sisi; Zhao, Weiquan; Su, Weici
Abstract: Water resource vulnerability in ecologically vulnerable karst areas is a key issue for regional sustainable development and the sustainable use of water resources. In this study, geographical information system (GIS) and remote sensing (RS) technology were employed to explore the vulnerability characteristics and spatial distribution of water resources in Guiyang City. The water resource vulnerability indicator in Guiyang ranged from 0.10 to 0.59, with an average value of 0.26. Yanglongsi Town, in Xifeng County, in the northern and main central urban area exhibited the highest water resource vulnerability, whereas Huaxi District in the south, and regions around Hongfeng Lake and Baihua Lake, in Qingzhen City, exhibited the lowest water resource vulnerability. Water resource vulnerability was predominantly mild, accounting for 35.85% of the total land area, followed by moderate (28.99%), with some non-vulnerable areas (13.60%) and very few extremely vulnerable areas (3.20%). Compared with traditional methods, the proposed index selection and assessment methods, based on GIS/RS, are both scientific and intuitive. In addition, the results are presented in detail, accurately reflecting the actual situation of water resource system vulnerability. HIGHLIGHTS: GIS spatial analysis technology was better in identifying the characteristics and spatial differences in water resource vulnerability than traditional assessment methods. The spatial distribution of water resources and water resource vulnerability in Guiyang is highly uneven. The water resource vulnerability index of Guiyang ranged from 0.10 to 0.59, and predominantly belonged to the mildly vulnerable category. Graphical Abstract